Clinical factors associated with in-hospital mortality among patients with cardiogenic shock admitted to the cardiology department of Ayub Teaching Hospital - Saif, Sardar Adnan; khan, Mati ullah; Ahmed, Bilal; Iqbal, Malik Zahid; Shah, Yasir Ali; Mehmood, Nasir (International Journal of Pathology, 2026)
Background: Cardiogenic shock (CS) is the most common complication of acute myocardial infarction. Our aim is to define the rate of in-hospital mortality and to evaluate the chosen clinical variables that relate to mortality in patients with cardiogenic shock. Methods: A Hospital based descriptive observational study was conducted at the Department of cardiology, Ayub teaching hospital, Abbottabad from June 2025 to December 2025.There were 129 patients with cardiogenic shock aged 40-80 years, both male and females. Patients in cardiogenic or non-cardiogenic shock (e.g. septic, hypovolemic or anaphylactic shock), end-stage renal or hepatic failure, post cardiac surgical status, traumatic cardiac injury, pregnant or lactating women were excluded. During the admission process, demographic and clinical data such as age, sex, body mass index, symptoms duration, smoking status, socioeconomic status, occupation, education level, and location were taken in a systematic manner. Hospital follow-ups were done with the admitted patients throughout the hospital stay and the outcome was the in-hospital mortality. The relationship between the chosen clinical factors and mortality were determined. Results: 35 (27.13%) patients were noted to die in-hospital. Among patients who died, male sex was present in 24 (68.57%), advanced age in 13 (37.14%), diabetes mellitus in 16 (45.71%), hypertension in 22 (62.86%), and obesity in 14 (40.0%). Comparison between mortality and survival groups on variables with denominations: There was no statistically significant difference in mortality and survival at p<0.05; hypertension exhibited a non-significant tendency towards increased mortality (OR 2.01, 95% CI 0.90-4.45, p=0.084). Conclusion: Older age, male sex, diabetes mellitus, hypertension and obesity were found among patients with in-hospital mortality although the comparative analysis at hand failed to prove these factors to be independent predictors.